PENAMBANGAN MARMER PADA PT. MAKASSAR MARMER MULIAINDAH KABUPATEN MAROS - Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2018)
Mining is the extraction of valuable minerals from the earth. Marble recovered by mining process. Marble is usually used as a building material. PT. Makassar Marmer Muliaindah is a private company, that is actively operating in marble mining in Indonesia. The mining system applied by PT. Makassar Marmer Muliaindah is Open Pit System with Quarry method. Phases of mining activities conducted by PT. Makassar Marmer Muliaindah include clearing, stripping, drilling, cutting, block splitting, block release, block refinement, loading, hauling and stocking.